ANALISIS KUALITAS PERAIRAN PANTAI SEI NYPAH KECAMATAN PERBAUNGAN KABUPATEN SERDANG BEDAGAI PROVINSI SUMATERA UTARA Analisist Water Quality in Sei Nypah Beach Serdang Bedagai District North Sumatera Province - Rizki Eka Putra; Budi Utomo; Ahmad Muhtadi (AQUACOASTMARINE, 2016)
Sei Nypah beach are located in the eastern coast of Sumatra, it has a variety ofactivities that affect the water quality. Information and understanding of environmentalchange is indispensable in ecosystem monitoring efforts.This research aims todetermine the status of Sei Nypah’s the water quality. This research had been conductedon May to Juny 2015 in Sei Nypah Beach, Serdang Bedagai District, North SumateraProvince. There are three station observed, Station 1 : aqua culture activities area;station 2 : agriculture activities area; and station 3: tourism activities area. Samplingwas done three time within 2 months. The value of physical and chemical parameters ofwater include temperature from 29,2 – 31,9 oC, turbidity 2 – 8 mg/l, pH 7,4 – 8,5,salinity 25 – 30 o/oo, DO 7,6 – 8 mg/l, BOD 0,6 – 1,7 mg/l, COD 11,12 – 18,36 mg/l,nitrate 0,0029 – 0,0041 mg/l, and phosphate 0,015 – 0,075. Sei Nypah’s water quality topollution index and storet method for station 1, station 2, and station 3 according werecatagorized to class lightly polluted.Keywords : Sei Nypah Beach, Pollution Index, Storet.